Research on organisational spaces - Pachura, Piotr (Zarządzanie strategiczne w dobie cyfrowej gospodarki sieciowej, 2020)
The aim of the study is to present the results of research in the field of verification of the theoretical model of space in the context of the functioning of the organization. Space has been recognized as an important cognitive category in the processes of interpreting the behavior of contemporary organizations, and at the same time this issue seems not very popular among researchers of organizations and management processes. Research methodology included: conceptual studies on the theoretical model of space (a priori model), expert studies, quantitative and qualitative techniques. The results of the research indicate that it is possible to propose an empirically verified model of space.